Managing upward : a partnership plan for employees and bosses - Hathaway, Patti (Crisp Pub. Menlo ParkUS, 1992)
Presents the satisfying manager/employee relationship as a contribution/compensation partnership. Stresses need for consonance between boss and employee priorities. Provides strategies for increasing effective communication. Identifies employee qualities which earn management's approval and provides techniques and strategies for coping with unsatisfactory 'boss behaviour'.